(untitled) (ҚазҰУ Хабаршысы. Дінтану сериясы, 2019)
The article analyzes religious and philosophical reflections on the basis of a study of the brief content of the narrative “Abushakhma”, based on the commandments and principles of the Holy Quran. The study of this article is closely intertwined with the main ideas of “Ruhani Zhanyru”. The problems that are addressed in the work are: the struggle with their nafs for the development of an individual, as well as religious measures and restrictions, the promotion of spiritual values that remain relevant in our society to this day. The authors analyze the events taking place in the work, such as: the commission of the reprehensible and blamed, violence and oppression, as well as a warning that all these and other offenses are punished according to Sharia law, which has become the basis of our traditions and life since ancient times. Following the analysis, a parallel was drawn with current problems in society, taking into account the degradation of the individual and society as a whole.